Improving the effectiveness of Field Epidemiology Training Programs: characteristics that facilitated effective response to the COVID-19 pandemic in Uganda - Julie R. Harris; Daniel Kadobera; Benon Kwesiga; Steven N. Kabwama; Lilian Bulage; Henry B. Kyobe; Atek A. Kagirita; Henry G. Mwebesa; Rhoda K. Wanyenze; Lisa J. Nelson; Amy L. Boore; Alex Riolexus Ario (BMC, 2022)
Abstract Background The global need for well-trained field epidemiologists has been underscored in the last decade in multiple pandemics, the most recent being COVID-19. Field Epidemiology Training Programs (FETPs) are in-service training programs that improve country capacities to respond to public health emergencies across different levels of the health system. Best practices for FETP implementation have been described previously. The Uganda Public Health Fellowship Program (PHFP), or Advanced-FETP in Uganda, is a two-year fellowship in field epidemiology funded by the U.S. Centers for Disease Control and situated in the Uganda National Institute of Public Health (UNIPH). We describe how specific attributes of the Uganda PHFP that are aligned with best practices enabled substantial contributions to the COVID-19 response in Uganda. Methods We describe the PHFP in Uganda and review examples of how specific program characteristics facilitate integration with Ministry of Health needs and foster a strong response, using COVID-19 pandemic response activities as examples. We describe PHFP activities and outputs before and during the COVID-19 response and offer expert opinions about the impact of the program set-up on these outputs. Results Unlike nearly all other Advanced FETPs in Africa, PHFP is delinked from an academic degree-granting program and enrolls only post-Master's-degree fellows. This enables full-time, uninterrupted commitment of academically-trained fellows to public health response. Uganda's PHFP has strong partner support in country, sufficient technical support from program staff, Ministry of Health (MoH), CDC, and partners, and full-time dedicated directorship from a well-respected MoH staff member. The PHFP is physically co-located inside the UNIPH with the emergency operations center (EOC), which provides a direct path for health alerts to be investigated by fellows. It has recognized value within the MoH, which integrates graduates into key MoH and partner positions. During February 2020-September 2021, PHFP fellows and graduates completed 67 major COVID-related projects. PHFP activities during the COVID-19 response were specifically requested by the MoH or by partners, or generated de novo by the program, and were supervised by all partners. Conclusion Specific attributes of the PHFP enable effective service to the Ministry of Health in Uganda. Among the most important is the enrollment of post-graduate fellows, which leads to a high level of utilization of the program fellows by the Ministry of Health to fulfill real-time needs. Strong leadership and sufficient technical support permitted meaningful program outputs during COVID-19 pandemic response. Ensuring the inclusion of similar characteristics when implementing FETPs elsewhere may allow them to achieve a high level of impact.